The moderating role of trust in business to business electronic commerce (B2B EC) adoption - Alsaad, Abdallah K.H.; Mohamad, Rosli; Ismail, Noor Azizi (Elsevier, 2017)
This paper revisited the role of trust in Business to Business Electronic Commerce (B2B EC) settings in Jordan, using an alternative view on trust suggesting that this variable has a moderating effect rather than having a direct impact on the intentions of firms to adopt B2B EC.An interactionist model among trust and technological, organizational, and environmental factors was developed. A survey of 239 supply chain managers in Jordan was used to test the proposed model. Analyzed data shows that the moderating impact of trust was significant in one path, which was perceived desirability (stemming from the diffusion of innovation theory and representing the technological view). Trust did not moderate the impacts of organizational and environmental variables.The findings provided insights into how existing relationships between trading partners may not be flexible enough to absorb new technology.In a context in which trust beliefs are well established and critical such as Jordan, the flexibility of firms in responding to adoption motivations may be hampered rather than enabled.